International law and the role of APEC in the gobernance of economic cooperation within the Asia Pacific region - Davidson, Paul J. (2008)
The cumbersome administrative process of trading in the Asia Pacifi c region has lead to propose the creation of a Free Trade Area of the Asia Pacifi c Region (FTAAP), as part of the governance structure. In this respect, the Asia Pacifi c Economic Cooperation (APEC) would play a major role regarding the setting of guidelines for economic cooperation and a free and open approach to investments. It is also provided that APEC’s legal framework may be applied to the economic activities which have not been regulated by other international agreements, offering advantages as adapting to the real conditions of each state and the standardization of the already existing regulations. However, this non-binding framework, (soft law), does not foreclose, but complements the OMC’s binding legal framework (hard law).